2018
DOI: 10.3390/ijerph15122793
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Sport Participation, Body Composition, Physical Fitness, and Social Correlates Among Adolescents: The PAHL Study

Abstract: Background: Evidence suggests that social support impacts on participation in sport or physical activity (PA), and is associated with health benefits, although the link is complex and not well understood. The study aim was to examine whether participation in organized sports is related to body composition, physical fitness, and social correlates for PA. Methods: Cross-sectional data on 238 adolescents (90 boys and 148 girls), mean age 14.9 ± 0.8 years, who were participants in the Physical Activity and Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 56 publications
0
37
0
Order By: Relevance
“…Recent research has suggested that sport participation is associated with improved body composition and cardiovascular fitness when compared with nonsport participants. 27 Marques et al 28 clearly link those with greater sport participation to greater levels of moderate to vigorous physical activity. Phillips and Young 29 have also linked sport participation to both increases in energy expenditure and physical fitness for inner city females.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has suggested that sport participation is associated with improved body composition and cardiovascular fitness when compared with nonsport participants. 27 Marques et al 28 clearly link those with greater sport participation to greater levels of moderate to vigorous physical activity. Phillips and Young 29 have also linked sport participation to both increases in energy expenditure and physical fitness for inner city females.…”
Section: Discussionmentioning
confidence: 99%
“…This finding aligns with a previous qualitative study conducted among girls where the researchers found a sense of self when active (such as being motivated to be active, enjoying PA, being confident in PA skills, and having PA skills judged by peers), and changes in social support from peers and family during the transition were related to their participation in PA [ 9 , 15 ]. In addition, it is well-established that the influence of peers increases during adolescence and influences adolescents’ PA [ 34 , 35 , 36 , 37 , 38 , 39 ]. Similarly, our study showed peers influenced PA participation after transition in a sample of boys and girls, but we also found athletic identity was in a state of flux during the transition.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the environmental factors that influence adolescents’ levels of PA during the transition from elementary to secondary school is complex as this study identified a number of intrapersonal and environmental factors that changed during this period. Given our understanding of the environmental factors that influence adolescents’ PA [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 54 , 55 , 56 ], it was not surprising that changes in the school, social, and household environments were highlighted as influencing adolescents’ PA during transition. Studies that examine factors associated with youth PA during the transition from elementary school to secondary school are relatively rare, and this paper addresses an important gap in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, targeting family and peers in promoting active lifestyles should be considered with caution. The actual evidence suggests that social support positively affects the PA, although the association is still unclear and supported by mixed evidence [ 121 , 122 , 123 , 124 , 125 ]. Community interventions should take into consideration the whole and complex choice architecture of individuals, considering both the individual’s family and the specific cultural and social contexts and dynamics [ 57 , 126 ].…”
Section: Discussionmentioning
confidence: 99%